2022
DOI: 10.1111/myc.13444
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pulmonary aspergillosis in patients with active pulmonary tuberculosis with persisting symptoms in Uganda

Abstract: Background The occurrence of chronic pulmonary aspergillosis (CPA) among drug sensitive pulmonary tuberculosis (PTB) patients on optimal therapy with persistent symptoms was investigated. Methods We consecutively enrolled participants with PTB with persistent pulmonary symptoms after 2 months of anti‐TB treatment at Mulago Hospital, Kampala, Uganda, between July 2020 and June 2021. CPA was defined as a positive Aspergillus‐specific IgG/IgM immunochromatographic test (ICT), a cavity with or without a fungal bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…We observed no significant statistical difference in the rate of CPA in HIV-positive patients and CPA in HIV-negative patients (6.8% vs 10.9%), contrary to other studies. 6 , 16 , 22 , 33 Though Aspergillus serology was positive in less than 10% of our screened patients, it contributed to greater than 90% of CPA diagnosis. One CPA patient who was HIV-positive had a negative Aspergillus IgG and IgM LFA result.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We observed no significant statistical difference in the rate of CPA in HIV-positive patients and CPA in HIV-negative patients (6.8% vs 10.9%), contrary to other studies. 6 , 16 , 22 , 33 Though Aspergillus serology was positive in less than 10% of our screened patients, it contributed to greater than 90% of CPA diagnosis. One CPA patient who was HIV-positive had a negative Aspergillus IgG and IgM LFA result.…”
Section: Discussionmentioning
confidence: 77%
“…The current study revealed a CPA prevalence of 9.7% among patients presenting with presumed PTB. Varying rates have also reported in Uganda 22 and Nigeria, 6 Iran, 23 Pakistan, 24 Indonesia, 15 , 21 Uganda, 16 and Brazil 25 largely due to difference in study designs, population, investigations, and sampling methods. Also, the present study identified 50% prevalence of CPA in patients with prior PTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note, however, that their cohort included at least 42% new non-bacteriologically confirmed PTB cases, and some of them probably had CPA alongside other respiratory disorders, including asthma and chronic pulmonary obstructive disease (COPD) as an underlying condition. Similarly, another study in Uganda reported ~20% CPA incidence among PTB patients with persisting symptoms after 2 months of TB treatment [6]. In a recently published study, a possible PTB-CPA coinfection was reported, but there are still doubts with regard to the existence of a true PTB infection [17].…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of CPA as a sequel of PTB worldwide was estimated at 1.2 million in 2011 [ 4 ]. Several cross-sectional studies have been conducted on CPA as a secondary infection of PTB in different countries, and they have reported varying rates [ 5 , 6 , 7 , 8 , 9 ]. However, none of these studies have solely focused on bacteriologically confirmed PTB, and so, they may have included individuals without prior PTB, and this may not be a true definition of the post-PTB complications.…”
Section: Introductionmentioning
confidence: 99%